An Object-Oriented Frameworks-based Architecture for Decision Support Systems - Karin Becker; François Bodart (CLEI Electronic Journal, 1998)
Reusability is considered to be the key for achieving productivity and quality in software, and much has been claimed about the particular contributions of the object-oriented paradigm towards the achievement of these goals. Object-oriented frameworks are coarse-grained reuse units, composed of a set of classes specifically designed to be refined and used as a group. In this paper, we discuss the nature of frameworks necessary to build a particular type of systems, namely Decision Support Systems (DSS), and their organization in a generic OO DSS multi-layer architecture. DSS are systems intended to improve the effectiveness of decision making, but information technologies can only have a major impact on decision making if techniques allowing the easy and rapid development of DSS are available. Much benefit is expected in terms of easiness and rapidity of development by constructing DSS from domain-oriented reusable components, as well as in terms of quality of DSS in this way developed.